(untitled) (Kairaranga, 2018)
Recently, Alison Kearney interviewed the New Zealand Children’s Commissioner, Judge Andrew Becroft. In this interview, Commissioner Becroft discusses the role and priorities of the Office of the Children’s Commissioner, the importance of listening to the voice of young people, and his views in relation to the role of education in meeting the needs of all children, particularly those who experience exclusion and marginalisation from and within school and society.